A semi-empirical correlation for the thermal conductivity of frost. (October 2015) - Negrelli, Silvia; Hermes, Christian J.L.
Abstract: The present work is aimed at advancing an improved correlation for the thermal conductivity of frost. The analysis was conducted based on the weighted geometric mean of the thermal resistances of moist air and ice crystals, thus setting the theoretical background for a dimensionless model for the thermal conductivity as a function of the porosity of the frosted medium. Experimental data obtained elsewhere for a wide wall surface temperature span (from −30 °C to −4 °C) were employed to fit the model, coming up with a semi-empirical correlation for the thermal conductivity of frost valid for porosities ranging from 0.5 to 0.95. Comparisons of the proposed correlation with the experimental data showed that it is able to predict 81% of the data points (153 out of 188) within the 15% thresholds. Comparisons with other correlations available in the open literature are also reported. Highlights: An improved correlation for the thermal conductivity of frost is advanced. The correlation is based on the geometric mean of air and ice conductivities. Experimental data obtained elsewhere were employed to fit the model. The correlation is able to predict 81% of the data within 15% bounds. Comparisons with other correlations are also reported.